Diversity in Xanthophyll Cycle Pigments Content and Related Nonphotochemical Quenching (NPQ) Among Microalgae: Implications for Growth Strategy and Ecology. Issue 2 (5th February 2020) - Lacour, Thomas; Babin, Marcel; Lavaud, Johann
Abstract : Xanthophyll cycle‐related nonphotochemical quenching (NPQ), which is present in most photoautotrophs, allows dissipation of excess light energy. Xanthophyll cycle‐related NPQ depends principally on xanthophyll cycle pigments composition and their effective involvement in NPQ. Xanthophyll cycle‐related NPQ is tightly controlled by environmental conditions in a species‐/strain‐specific manner. These features are especially relevant in microalgae living in a complex and highly variable environment. The goal of this study was to perform a comparative assessment of NPQ ecophysiologies across microalgal taxa in order to underline the specific involvement of NPQ in growth adaptations and strategies. We used both published results and data acquired in our laboratory to understand the relationships between growth conditions (irradiance, temperature, and nutrient availability), xanthophyll cycle composition, and xanthophyll cycle pigments quenching efficiency in microalgae from various taxa. We found that in diadinoxanthin‐containing species, the xanthophyll cycle pigment pool is controlled by energy pressure in all species. At any given energy pressure, however, the diatoxanthin content is higher in diatoms than in other diadinoxanthin‐containing species. XC pigments quenching efficiency is species‐specific and decreases with acclimation to higher irradiances. We found a clear link between the natural light environment of species/ecotypes and quenching efficiency amplitude. The presence of diatoxanthin or zeaxanthin at steady state in all species examined at moderate and high irradiances suggests that cells maintain a light‐harvesting capacity in excess to cope with potential decrease in light intensity.